The Gospel of Thomas : introduction and commentary - Gathercole, Simon J. (Texts and Editions for New Testament Study, 2014)
In this new commentary on the controversial Gospel of Thomas , Simon Gathercole provides the most extensive analysis yet published of both the work as a whole and of the individual sayings contained in it. This commentary offers a fresh analysis of Thomas not from the perspective of form criticism and source criticism but seeks to elucidate the meaning of the work and its constituent elements in its second-century context. With its lucid discussion of the various controversial aspects of Thomas, and treatment of the various different scholarly views, this is a foundational work of reference for scholars not just of apocryphal Gospels, but also for New Testament scholars, Classicists and Patrologists.